2018
DOI: 10.1080/17437199.2018.1463166
|View full text |Cite
|
Sign up to set email alerts
|

The weight of fatherhood: identifying mechanisms to explain paternal perinatal weight gain

Abstract: Men appear to gain weight during the transition to parenthood, and fathers are heavier than non-fathers. Paternal perinatal weight gain may set weight trajectories in midlife and have long-term health implications. Since men do not undergo the physical demands of pregnancy and breastfeeding, the specific mechanisms underlying weight gain in new fathers warrant investigation. This review aims to stimulate research on paternal perinatal weight gain by suggesting testable potential mechanisms that (1) show change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 110 publications
1
30
0
Order By: Relevance
“…In a comprehensive review of parenthood and fathers' and mothers' health, Saxbe, Rossin‐Slater, and Goldenberg () reported that the transition to parenthood is an inflection point for body weight trajectories. Mechanisms that seem to influence fathers' weight gain during the transition to fatherhood include changes in sleep, physical activity, testosterone, and stress (Saxbe et al, ). A cross‐national study of fathers in six Asian countries found that fathers who were more involved with their children from infancy through adolescence were more likely to report positive general health and life satisfaction and less likely to report depression (Chan, Emery, Fulu, Tolman, & Ip, ).…”
Section: Significant Developmentsmentioning
confidence: 99%
“…In a comprehensive review of parenthood and fathers' and mothers' health, Saxbe, Rossin‐Slater, and Goldenberg () reported that the transition to parenthood is an inflection point for body weight trajectories. Mechanisms that seem to influence fathers' weight gain during the transition to fatherhood include changes in sleep, physical activity, testosterone, and stress (Saxbe et al, ). A cross‐national study of fathers in six Asian countries found that fathers who were more involved with their children from infancy through adolescence were more likely to report positive general health and life satisfaction and less likely to report depression (Chan, Emery, Fulu, Tolman, & Ip, ).…”
Section: Significant Developmentsmentioning
confidence: 99%
“…Paternal perinatal depression influences the father–child relationship and is related to less optimal relationships between couples as well as to maternal depression (Paulson et al, ), doubling the risk for unfavorable child outcomes. As in mothers, in fathers, hormonal imbalances may be related to postpartum depression (Saxbe et al, ), but lack of sufficient sleep may also play a role: 35% of parents with children under age 2 report that they get only 5–6 hr of sleep per night (Krueger & Friedman, ). Identifying risk factors for paternal perinatal depression is an important step toward prevention, ideally before the baby is born.…”
Section: A Biobehavioral Model Of Emergent Fatherhoodmentioning
confidence: 99%
“…In addition, for both men and women, the onset of parenthood, while often joyful, is frequently accompanied by heightened stress and potentially harmful changes in behaviour including decreases in physical activity [ 22 25 ]. Such changes in behaviour over the transition to parenthood may have a long-lasting impact in shaping health trajectories into midlife [ 26 ].…”
Section: Introductionmentioning
confidence: 99%